2013
DOI: 10.5435/jaaos-21-10-613
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Infiltration and Rotator Cuff Atrophy

Abstract: Moderate to severe fatty infiltration and rotator cuff atrophy are commonly associated with poor clinical outcomes and failed rotator cuff repair. Numerous animal and human studies have attempted to elucidate the etiology of fatty infiltration and rotator cuff atrophy. Mechanical detachment of the tendon in rotator cuff tears is primarily responsible. Suprascapular nerve injury may also play a role. CT, MRI, and ultrasonography are used to evaluate severity. The Goutallier staging system is most commonly used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 46 publications
3
112
0
4
Order By: Relevance
“…Fatty infiltration has been shown to be distributed non- uniformly throughout the muscle belly, 8,29 challenging the rationale of using a single image to evaluate fatty infiltration. 14 Jo and Shin 30 showed that new baseline images are needed following surgical repair because surgery moves the muscle and changes its appearance in the MR image. Additionally, the large image slices (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatty infiltration has been shown to be distributed non- uniformly throughout the muscle belly, 8,29 challenging the rationale of using a single image to evaluate fatty infiltration. 14 Jo and Shin 30 showed that new baseline images are needed following surgical repair because surgery moves the muscle and changes its appearance in the MR image. Additionally, the large image slices (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these assessment techniques are applied to identify surgical candidates. 5,7,11,14 Single-image assessments may mislead clinicians because they do not account for variation in three-dimensional muscle morphology. Both atrophy and fatty infiltration occur with aging but are separate processes 6 and the results of increased muscle atrophy without marked increases in fatty infiltration volume following a RCT support that report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty infiltration and tear can be better analyzed in magnetic resonance imaging. The presence and severity of fatty infiltration have been associated with increasing age, tear size, degree of tendon retraction, number of tendons involved and traumatic tears [86] .…”
Section: Clinical Assessment Of Shoulder Tendinopathymentioning
confidence: 99%
“…The injured rotator cuff muscles (supraspinatus and infraspinatus in particular) show abnormal fibrosis, fatty infiltration, and changes in fat deposits on CT, MRI, and ultrasound. 66,77 These changes can be significant and may influence the outcome of the repair process. 47 While it is not known how the specific changes occur at the cellular level, in humans the SC or skeletal muscle progenitors are higher in number in partialthickness rotator cuff tears compared to noninjured and full-thickness tears.…”
Section: Etiology Of Mfi and Cellular Dynamicsmentioning
confidence: 99%